Comparing the effects of acupressure and aromatherapy with peppermint essential oil on the quality of recovery of patients undergoing laparoscopic cholecystectomy: A randomized controlled trial - Behzad Imani; Fatemeh Zare; Salman Khazaei (Shahrekord University of Medical Sciences, 2024)
Introduction: Complementary medicine presents a viable avenue for mitigating side effects after surgery. This study aimed to compare the effects of acupressure and peppermint essential oil on the quality of recovery in patients undergoing laparoscopic cholecystectomy (LC). Methods: In this clinical trial, 210 patients referred to the Besat and Beheshti hospitals in Hamadan, Iran, were included. After giving their informed consent and completing the demographics survey, they were randomly assigned to 3 equal groups of control, peppermint essential oil, and acupressure. The study primarily assessed recovery quality through a 15- item questionnaire and secondarily evaluated postoperative nausea and satisfaction. Data were analyzed using Kruskal-Wallis, Wilcoxon, and Friedman tests in SPSS 23. Results: In pre-intervention, there was no significant difference between the groups in the total score of recovery quality, nausea, and demographic data. There was a significant increase in the quality of recovery score in the acupressure group when compared to the peppermint group on the second postoperative day (P<0.001). In post-intervention, the mean score of nausea improvement in the control group was significantly less than those of the peppermint and acupressure groups (P<0.05). However, neither the acupressure nor peppermint groups displayed a significant reduction in nausea severity (P=0.439). Furthermore, the patient's satisfaction in the acupressure group was significantly higher than that of other groups on the second postoperative day (P<0.001). Conclusion: The administration of acupressure was found to be successful in improving recovery quality, patient satisfaction, and mitigating nausea compared to peppermint and standard treatment.